Anorectal malformation combined with Hirschsprung's disease: a case report - Fan, Jiansen; Liu, Mingkun; Lin, Yu; He, Yuanbin; Fang, Yifan (Frontiers in Pediatrics, 2023)
Anorectal malformation (ARM) and Hirschsprungs disease (HSCR) are frequently associated with other congenital malformations, but rarely with one another. We describe the case of a child with intermediate anorectal malformation who underwent ARM correction. This child experienced recurrent postoperative symptoms, including intestinal obstruction, nutrition intolerance, and weight loss. The child was diagnosed with Hirschsprung's disease by colon barium contrast and pathological findings from a rectal mucosal biopsy, and subsequently underwent pull -through procedure after conservative treatment failed. After six months of postoperative follow-up, the patient still experiences occasional episodes of enteritis, but the symptoms are substantially less severe than they were before surgery, and the patient's weight is slowly increasing. We described a case of a kid who had ARM combined with HSCR,offering doctors a point of reference.Although the association between ARM and HSCR is uncommon, severe constipation or enteritis following complete correction of ARM in the absence of anal stricture should prompt consideration for HSCR. Before the second stage of ARM surgery, pay close attention to the barium enema examination, as an abnormal shape may indicate the presence of HSCR.